Innovation in Augmented Reality-Based Chemical Bonding Learning Media to Support Interactive Learning - Ade Irma Nur; Fauzia Amina; Tiwi Desrina; Tianur Secha (Journal of Chemical Learning Innovation, 2026)
Purpose of the study: This study aims to determine students’ responses toward an interactive learning media based on augmented reality technology on chemical bonding material, focusing on usability, visualization, material benefits, language clarity, and potential impact in supporting interactive learning experiences. Methodology: This study employed the Warsita development model consisting of design, production, and evaluation stages. The developed media included an augmented reality application integrated with a marker book. Data were collected through a structured questionnaire consisting of 40 items administered to 40 students. Validation involved media and subject experts, and data were analyzed using percentage techniques and interpretation criteria. Main Findings: Students showed positive responses toward the augmented reality-based interactive learning media, categorized as good overall. High acceptance was reflected in usability and illustration aspects, while material benefits, grammar, and future impact were also positively rated. The media demonstrated feasibility for classroom use with minor improvements needed for long-term learning engagement. Novelty/Originality of this study: This study presents an augmented reality-based interactive learning media specifically designed for chemical bonding with integrated marker books and application features. It emphasizes students’ response evaluation across multiple aspects, providing empirical insight into user acceptance and contributing to the development of more effective and engaging chemistry learning media.